1996
DOI: 10.1149/1.1836988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microstructure of Carbon Support in the Catalyst Layer on the Performance of Polymer‐Electrolyte Fuel Cells

Abstract: The influence of convection and interfacial-reaction resistance on the response of microsensors, including the effects of: (i) fluid flow rates; (ii) reactant (to be sensed) concentration and diffusion coefficient; (iii) fluid conduit and microsensor size; and (iv) sensor potential and interfacial-reaction resistance, are clarified. For steady-state convective diffusion to a niicrodisk sensor, it is shown that sensor response is a monotonic function of two dimensionless groups: the Péclet number Pe, which char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
191
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 325 publications
(196 citation statements)
references
References 7 publications
2
191
3
Order By: Relevance
“…0, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]However, the optimum N/C ratios are found to be lower, namely 0.7 and 0.5 for the VC and HG supports, respectively. The optimum N/C value using VC as catalyst support is essentially the same as reported by Liu and Song et al [19,20] i.e.…”
Section: Original Research Papermentioning
confidence: 99%
See 4 more Smart Citations
“…0, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]However, the optimum N/C ratios are found to be lower, namely 0.7 and 0.5 for the VC and HG supports, respectively. The optimum N/C value using VC as catalyst support is essentially the same as reported by Liu and Song et al [19,20] i.e.…”
Section: Original Research Papermentioning
confidence: 99%
“…This difference may be due to differences in the pore-size distribution of the supports. Uchida et al [9] reported that improvement of DMFC performance can be achieved using a carbon support with a large pore volume, which is able to distribute the Nafion ionomer over the Pt particles inside the carbon support agglomerates. Figure 9 shows the Nyquist plots for the total cell impedance using KB-60, VC-60 and HG-60 cathode catalysts.…”
Section: Original Research Papermentioning
confidence: 99%
See 3 more Smart Citations